2014
DOI: 10.7224/1537-2073.2013-032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 2-Week Trial of Functional Electrical Stimulation on Gait Function and Quality of Life in People with Multiple Sclerosis

Abstract: These results suggest that use of FES can significantly improve gait speed, decrease the impact of MS on walking ability, and improve QOL in people with MS-related footdrop even over a short period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 26 publications
1
33
0
1
Order By: Relevance
“…16 The orthotic effect was manifested in an 18.3 % improvement in performance, both at baseline and after 2 weeks of FES use, suggesting that the orthotic benefits of FES can occur prior to habituation.…”
Section: Functional Electrical Stimulation On Gait Effects Gait Speedmentioning
confidence: 95%
See 4 more Smart Citations
“…16 The orthotic effect was manifested in an 18.3 % improvement in performance, both at baseline and after 2 weeks of FES use, suggesting that the orthotic benefits of FES can occur prior to habituation.…”
Section: Functional Electrical Stimulation On Gait Effects Gait Speedmentioning
confidence: 95%
“…5 Overall, a majority of the studies observing the effects on walking performance have reported orthotic effects, [4][5][6][7][8][9]13,14,16,20,22,24 and in some cases a total orthotic benefit after weeks of FES device use 8,24 with one study noticing this benefit only after 2 weeks. 16 Training effects have been consistently reproduced in nonprogressive neurologic conditions, such as stroke and spinal cord injury populations. This has not been the case in MS patients, and this difference has been attributed in part to the progressive course of MS. One publication, comparing stroke and MS patients, found that a training effect was present only in the stroke patient group.…”
Section: Functional Electrical Stimulation On Gait Effects Gait Speedmentioning
confidence: 99%
See 3 more Smart Citations